Role and regulation of CTEN in colorectal cancer - Alfahed, Abdulaziz/AF (2020)
C-terminal tensin-like (CTEN), also called Tensin4 (TNS4), is the fourth member of the tensin family. The function of CTEN is tissue dependent; it acts as an oncogene in numerous cancers, including colorectal cancer (CRC) but appears to be a tumour suppressor in prostate cancer. While it is barely detectable in normal colorectal tissues, CTEN is upregulated in early-stage colorectal cancer (CRC). CTEN induces invasion and migration in CRC cell lines; however, the mechanisms by which CTEN exerts these effects are poorly understood. This thesis investigated (i) the regulation of CTEN and (ii) the biological function of specific protein domains in CTEN using CRC cell lines and induced pluripotent stem cells (iPSCs). CTEN has been reported to interact with β-catenin in CRC cell lines and form a complex in the nucleus. The oncogenic activity of CTEN and β-catenin, independently, in CRC is well established. However, the biological function of the CTEN/β- interaction is unknown. Firstly, CTEN deletion mapping was used to identify the molecular sites responsible for the CTEN/β- catenin interaction. Co-immunoprecipitation (Co-IP) assays revealed that the N-terminus of CTEN binds β-catenin. Moreover, functional assays demonstrated that the CTEN/β- catenin interaction was not required for CTEN-induced migration and invasion in CRC cells. Upregulation of CTEN and Wnt pathway activation are early events in CRC and induce cancer stemness. β-catenin interacts with CTEN and is a downstream target of the Wnt pathway. To study the involvement of CTEN in the Wnt pathway, the levels of CTEN and β-catenin were modulated in CRC cells and in normal fibroblasts. Western blotting for CTEN and active β- catenin showed that β-catenin positively regulates CTEN expression in both CRC cells and normal fibroblasts. Wnt pathway activation drives differentiation of iPSCs into the endoderm that forms colonic tissue and other digestive organs. CTEN is expressed in iPSCs, but CTEN expression and regulation had not been investigated in iPSCs. To explore CTEN expression during Wnt-induced iPSC differentiation, iPSCs were treated with Wnt activators or a Wnt inhibitor. Analysis of CTEN expression showed CTEN is downregulated during Wnt-induced differentiation of iPSCs into endoderm. Thus the relationship between Wnt signalling and CTEN is different in pluripotent cells to that in mature tissue. CTEN is a common feature in the signalling pathway of numerous growth factors and the oncogenic functions of several growth factors may be dependent on CTEN activty. CTEN induces invasion, migration and the EMT in CRC; however, these oncogenic mechanisms are poorly understood. CTEN contains a SH2 domain and can translocate to the nucleus in CRC cells. SH2 domains are important for localisation to focal adhesions in the cytoplasm. To investigate how CTEN functions as an oncogene in CRC, CTEN deletion mutant constructs lacking the SH2 domain and a predicted nuclear localisation signal were created. The ability of CTEN to induce migration and invasion in CRC cells was dependent on the SH2 domain and independent of nuclear localisation of CTEN. Moreover, preliminary results indicated that CTEN may play a role in the hypoxia-induced epithelial- mesenchymal transition. In summary, this thesis highlights number of novel findings regarding the regulation and function of CTEN as an oncogene in CRC and revealed the pattern of CTEN expression during Wnt- induced differentiation of iPSCs into endoderm. This work provides a basis for further investigation of the regulation and biological function of CTEN in CRC, iPSCs and other models.